Cost of skeletal complications from bone metastases in six European countries - Pereira, J; Body, J-J; Gunther, O; Sleeboom, H; Hechmati, G; Maniadakis, N; Terpos, E; Acklin, Y P; Finek, J; von Moos, R (Journal of medical economics, 2016)
Objective Patients with bone metastases or lesions secondary to solid tumors or multiple myeloma often experience bone complications (skeletal-related events [SREs]-radiation to bone, pathologic fracture, surgery to bone, and spinal cord compression); however, recent data that can be used to assess the value of treatments to prevent SREs across European countries are limited. This study aimed to provide estimates of health resource utilization (HRU) and cost associated with all SRE types in Europe. HRU data were reported previously; cost data are reported herein. Methods Eligible patients from 49 centers across Austria (n = 57), the Czech Republic (n = 59), Finland (n = 60), Greece (n = 59), Portugal (n = 59), and Sweden (n = 62) had bone metastases or lesions secondary to breast, lung, or prostate cancer, or multiple myeloma, and ≥1 index SRE (a SRE preceded by a SRE-free period of ≥ 6.5 months). SRE-related costs were estimated from a payer perspective using health resource utilization data from patient charts (before and after the index SRE diagnosis). Country-specific unit costs were from 2010 and local currencies were converted to 2010 euros. Results The mean costs across countries were €7043, €5242, €11,101, and €11,509 per radiation to bone, pathologic fracture, surgery to bone, and spinal cord compression event, respectively. Purchasing power parity (PPP)-adjusted mean cost ratios were similar in most countries, with the exception of radiation to bone. Limitations The overall burden of SREs may have been under-estimated owing to home visits and evaluations outside the hospital setting not being reported here. Conclusions All SREs were associated with substantial costs. Variation in SRE-associated costs between countries was most likely driven by differences in treatment practices and unit costs.
Keywords: Cost; Europe; Female; Bone Neoplasms; Skeletal-related events; ženské pohlaví; komprese míchy; Models, Econometric; lidé; Bone metastases; Evropa; ekonometrické modely; nádory kostí; Supportive care; výdaje na zdravotnictví; Male; fraktury spontánní; Aged; Health Services; lidé středního věku; senioři; mužské pohlaví; zdravotnické služby; Fractures, Spontaneous; Middle Aged; Spinal Cord Compression; Health Expenditures; Humans